Recordatus : uma solução móvel baseada em internet das coisas para suporte a adultos com TDHA - Fujiwara, Carlinha Santos (Universidade de Fortaleza, 2017)
Made available in DSpace on 2019-03-30T00:08:25Z (GMT). No. of bitstreams: 0 Previous issue date: 2017-12-29 === The ADHD (Attention Deficit Disorder and Hyperactivity) is a brain disorder and whose main characteristics are inattention, restlessness and impulsivity. It has its onset in childhood (it occurs in 3 to 5% of the children in the world), being able to accompany the individual throughout its life, although some symptoms become more soft throughout the time. In adults, most problems are related to the difficulty of organizing, planning, managing time, remembering dates, appointments, objects, among others. With the advancement of technology, several solutions have emerged to help our day-to-day life, as well as for peoples with some type of disability, giving them a greater autonomy. In this context, we have the IoT (Internet of Things), one of the solutions with great potential to provide this autonomy, since we can provide several devices, for example, to monitor our blood pressure or body temperature, without the need to be in a hospital. This work proposes a solution, based on IoT, to help the daily activities of an adult person with ADHD. For this, was developed a tool that is able to remember activities and possible lost objects. The evaluation carried out over the proposed solution was based on a questionnaire applied to specialized professionals. The results obtained so far, show that the tool has demonstrated a great potential to help people with ADHD.